The Ministry of Agriculture and Rural Development incorporated more A4NH evidence in implementation of nutrition-sensitive agriculture approaches in Viet Nam as part of their National Action Plan for Zero Hunger - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
In 2021, the Ministry of Agriculture and Rural Development started implementing A4NH-informed nutrition-sensitive agriculture approaches in 11 provinces as part of their Zero Hunger initiative.